PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA POKOK BAHASAN MATRIKS KELAS XI SMA/MA - Ikhsan Hardi (Departemen Matematika, 2021)
This study aims to develop Student Worksheets (LKPD) on the subject of the matrix for class XI SMA / MA by implementing Problem Based Learning (PBL) based learning. In addition, this study aims to analyze and describe the characteristics of the PBL-based LKPD on the subject of the valid and practical matrix of class XI SMA / MA. This development research uses the Plomp model which consists of three phases, namely the Preliminary Research phase, the Prototyping Stage, and the Assessment Phase. Based on the results of the validity data analysis, it shows that the PBL-based student worksheets on the subject of the matrix in terms of content feasibility, completeness of PBL components, language, presentation and graphics have a validity level of 83,65% with a very valid category. LKPD also met the practical criteria of the student response questionnaire results with a percentage of 87,22%. Based on these results, it can be concluded that the PBL-based student worksheets on the subject of the matrix for high school class XI students can be declared valid and practical. Keywords — Development, Student Worksheets, Problem Based Learning